2017
DOI: 10.3390/catal7070218
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Conversion of Carbohydrates to Furanic Derivatives in the Presence of Choline Chloride

Abstract: Abstract:The synthesis of furanic derivatives (5-hydroxymethylfurfural (HMF), furfural . . . ) from carbohydrates is of high interest for a wide range of applications. These reactions are carried out in the presence of various solvents, and among them choline chloride can be used. It is a salt that can form a low melting mixture with a carbohydrate (fructose, glucose . . . ) or a deep eutectic mixture with carboxylic acid. A review of the studies performed in the conversion of carbohydrates to furanic derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Interestingly, K D had a maximum value of 4 between 40 min and 60 min of reaction. This value is similar to, or even higher than, other investigations of biphasic systems, although they may have used different solvents [32][33][34].…”
Section: Chemical Reaction Model For the Conversion Of Sucrose To Hmfsupporting
confidence: 79%
“…Interestingly, K D had a maximum value of 4 between 40 min and 60 min of reaction. This value is similar to, or even higher than, other investigations of biphasic systems, although they may have used different solvents [32][33][34].…”
Section: Chemical Reaction Model For the Conversion Of Sucrose To Hmfsupporting
confidence: 79%
“…With optimized conditions identified in water (Table 1, entry 4) and in LMM (Table 2, entry 7), [19] we next studied the generality of the alcohol substrate for this oxidation reaction. As for the reactions in water, benzylic alcohol derivatives with a MeO group at the ortho ‐, meta ‐, and para ‐positions ( 1 b – d ) reacted smoothly, affording the corresponding aldehydes 2 b – d in 79–87 % yield (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…32,33 Therefore, in the present study, we try to obtain a better extraction of HMF using aqueous DES (ChCl-urea) and introducing NaCl into the aqueous solution. Jeŕome et al 34 indicated that the yield and selectivity of HMF can also be enhanced in aqueous ChCl solution using MIBK as the extraction solvent. Furthermore, to our best knowledge, there is still no liquid−liquid equilibrium (LLE) data available for the combination of systems containing HMF, aqueous DES (ChCl-urea) solution, and organic solvent in the absence and presence of NaCl.…”
Section: Introductionmentioning
confidence: 99%